Attempt to Synthesize Hindered 2, 4, 6‐Tri‐Aryloxy‐s‐Triazines: Bis(2, 4‐di‐tert‐Butylphenyl) Carbonate – Crystal Structure. Issue 5 (28th December 2017) - Noroozi Pesyan, Nader; Kashani, Elmira; Ghorbanzadeh, Kamaleh; Notash, Behrouz
Abstract : Some less hindered 2, 4, 6‐tri‐aryloxy‐ s ‐triazines were synthesized through the reaction of the corresponding phenols as a starting materials with cyanogen bromide (BrCN) to obtain the corresponding arylcyanates and then trimerized. Unexpectedly, 2, 4‐di‐ tert ‐butyl‐1‐cyanatobenzene derived from 2, 4‐di‐ tert ‐butylphenol did not trimerize but, indeed, yielded bis(2, 4‐di‐ tert ‐butylphenyl) carbonate. The structures of 2, 4, 6‐tri‐aryloxy‐ s ‐triazines and bis(2, 4‐di‐ tert ‐butylphenyl) carbonate were characterized by means of IR, 1 H, and 13 C NMR spectroscopies. Also the structure of the latter compound was studied by X‐ray crystallography. Abstract : Some less hindered 2, 4, 6‐tri‐aryloxy‐ s ‐triazines were synthesized through the reaction of the corresponding phenols as starting materials with cyanogen bromide (BrCN) to give the corresponding arylcyanates and then trimerized. Unexpectedly, 2, 4‐di‐ tert ‐butyl‐1‐cyanatobenzene derived from 2, 4‐di‐ tert ‐butylphenol did not trimerize but, indeed, yielded bis(2, 4‐di‐ tert ‐butylphenyl) carbonate.